2001
DOI: 10.1021/jm0102203
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Pyrrolidine-5,5-trans-lactams (5-Oxohexahydropyrrolo[3,2-b]pyrroles) as Novel Mechanism-Based Inhibitors of Human Cytomegalovirus Protease. 2. Potency and Chirality

Abstract: The stereospecific synthesis of a series of alpha-methylpyrrolidine-5,5-trans-lactam inhibitors of human cytomegalovirus (HCMV) protease is described. Examination of the SAR in this series has defined the size and chirality of the alpha-substituent, optimized the acyl substituent on the lactam nitrogen, and defined the steric constraint of this functionality. The SAR of the functionality on the pyrrolidine nitrogen of the trans-lactam has been investigated, and this has led to the discovery of potent serine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 17 publications
0
45
0
Order By: Relevance
“…77,79 Sulfonamide-based antivirals were also recently designed against the HCMV protease. 80 In contrast to the HIV PR discussed earlier, this enzyme belongs to the serine PR family, and together with similar proteases isolated from other herpes viruses, it is characterized by a particular catalytic triad, of the type His, His, Ser within the active site. 81 It was observed that a-methylpyrrolidine-5,5-trans-lactam derivatives of type 80 act as mechanism-based inhibitors of the HCMV dAla protease, acylating reversibly and in a timedependent manner the active site nucleophile Ser 132.…”
Section: H E R P E S V I R U S E S ( H S V a N D H C M V ) P R O T mentioning
confidence: 96%
See 2 more Smart Citations
“…77,79 Sulfonamide-based antivirals were also recently designed against the HCMV protease. 80 In contrast to the HIV PR discussed earlier, this enzyme belongs to the serine PR family, and together with similar proteases isolated from other herpes viruses, it is characterized by a particular catalytic triad, of the type His, His, Ser within the active site. 81 It was observed that a-methylpyrrolidine-5,5-trans-lactam derivatives of type 80 act as mechanism-based inhibitors of the HCMV dAla protease, acylating reversibly and in a timedependent manner the active site nucleophile Ser 132.…”
Section: H E R P E S V I R U S E S ( H S V a N D H C M V ) P R O T mentioning
confidence: 96%
“…Compounds of type 82 bind to this PR with the 6-Me group within the S 1 subsite, the N-4-cyclopropylcarbonyl moiety within the S 1 0 subsite and the bulky, hydrophobic arylsulfonylpyrrolidine-2-carbonyl moiety within the S 3 subsite. 80 Derivatives incorporating the dansyl-(S)-proline moiety in this position showed the best activity (IC 50 of 0.34 mM) and also specificity over related serine proteases (such as elastase, thrombin, or acetyl cholinesterase), which were inhibited with IC 50 values in the range of 10-200 mM.…”
Section: H E R P E S V I R U S E S ( H S V a N D H C M V ) P R O T mentioning
confidence: 96%
See 1 more Smart Citation
“…We ultimately focused on two types of functionalization: acylation (including phosphonylation and sulfonylation) and arylation. Additional possible N-functionalization reactions of a related bicyclic substrate have been summarized in the work of Borthwick et al (33).…”
mentioning
confidence: 99%
“…Organic compounds containing nitrogenheterocyclic rings are important compounds in medicinal chemistry. Recently, because of their specially pharmaceutical and biological activities, compounds with pyrrole rings such as dihydro-2-oxypyrroles and Biginelli [5] reactions for the synthesis of 3, 4-dihydropyrimidin-2-(1H)-ones derivatives have attracted much interest in the organic researches for example these compounds have been used as anticancer [6], calcium channel blockers, α-1a-antagonists [7], human cytomegalovirus ( HCMV) protease [8], they has been used as Pl-091 [9], many of number alkaloids with biological activities have pyrrole rings [10], And these rings have been used as UCS1025A [11]. In the recent years, several protocols for the preparation of these compounds that is including bronsted or lewis acid catalysts have been reported for example Cu(OAc) 2 [12], [Btto][p-TSA] [13], bakers , yeast [14], Calcium Fluoride [15], copper(II) tetrafluoroborate [16], hydrotalcite [17], TBAB [18], hexaaquaaluminium(III) tetrafluoroborate [19], copper(II)sulfamate [20], I 2 [21], AcOH [22], [n-Bu 4 3 [24], oxalic acid [25], ZrCl 4 [26], InCl 3 [27].…”
Section: Introductionmentioning
confidence: 99%